Passing exams : a guide for maximum success and minimum stress - Hamilton, Dawn. (London : Cassell, 1999)
This book is divided into three parts: Preparing for Exams; Taking Exams; Boosting Mental Performance.
Keywords: Education; Study; Test-taking skills; Study skills; Examinations -- Study guides